Long-term contextual memory in infant rats as evidenced by an ethanol conditioned tolerance procedure - Castelló, Stefanía Anabel (2017)
Conditioned tolerance can be conceptualized as a particular case of Pavlovian conditioning in which contextual cues play the role of the conditioned stimulus. Although the evidence is contradictory, it is frequently assumed that long-term contextual conditioning in pre-weanling rats is weak or even absent. This hypothesis comes from and is sustained mainly by behavioral studies that explored different contextual effects in 16–18 day-old rats using a fear-conditioning paradigm, but their conclusions are stated in terms of an immature (hippocampal-dependent) declarative memory system. The main goal of the present manuscript was based on a recent antecedent from our laboratory, to analyze whether context-dependent tolerance induced by ethanol during the pre-weanling period persists over time. Results showed that the context was able to modulate ethanol-induced tolerance in 2- and 3-week-old rats. Interestingly, contextual conditioned tolerance was stronger (in terms of persistence) during the third than during the second postnatal week. When subjects were tested 8 days after training, when the context presumably lost its influence over tolerance, the opposite effect emerged (sensitization). These results are important for the ethanol literature, adding new evidence of long-term retention of ethanol effects acquired during infancy, whilst also showing striking ontogenetic differences in the sensitivity to ethanol between the 2nd and 3rd postnatal weeks. Importantly, contextual information modulates the expression of these ethanol effects even eight days after training, a result that is particularly relevant to the discussion of the ontogeny of contextual memory.